Does good advice come cheap? - On the assessment of risk preferences in the lab and the field - Andrea Leuermann; Benjamin Roth (University of Heidelberg, Department of Economics, 2012)
Advice is important for decision making, especially in the financial sector. We investigate how individuals assess risk preferences of others given sociodemographic information or pictures. Both non-professionals and fi nancial professionals participate in this artefactual field experiment. Subjects mainly rely on the other's self-assessment of risk preferences and on gender when forming the belief about someone else's risk preferences. On average, subjects consider themselves to be more risk-tolerant than the person they evaluate. Subjects use their own risk attitude as a reference point for predicting others' risk preferences. This false consensus eff ect is less pronounced for young professionals than for senior and non-professionals. Furthermore, financial professionals predict risk preferences more accurately compared to non-professionals.
urn:nbn:de:bsz:16-opus-136310
Keywords: G02; D81; C91; 330; Risk Preferences; Financial Advice; Artefactual Field Experiment; Behavioral Finance; Risikopräferenz; Finanzanalyse; Anlageverhalten; Sozialer Status; Feldforschung